Coupling confinement activating cobalt oxide ultra-small clusters for high-turnover oxygen evolution electrocatalysis. Issue 32 (30th July 2018) - Cao, Linlin; Cao, Yuanjie; Liu, Xiaokang; Luo, Qiquan; Liu, Wei; Zhang, Wei; Mou, Xiaoli; Yao, Tao; Wei, Shiqiang
Abstract : Developing active electrocatalysts based on cost-efficient transition metal oxides for the oxygen evolution reaction (OER) is critical to renewable energy technology such as water electrolyzers. Abstract : Developing active electrocatalysts based on cost-efficient transition metal oxides for the oxygen evolution reaction (OER) is critical to renewable energy technology such as water electrolyzers. Here, we report an interfacial coupling and confinement approach to activate CoO x clusters on phosphorized carbon nitride as an efficient and durable OER electrocatalyst. X-ray absorption and theoretical insights demonstrate that a coordinatively unsaturated surface and strong coupling effect tailor the electronic structure of Co active sites with optimized OH − adsorption energy for oxygen evolution. The resulting hybrid delivers high OER activity, reaching 10 mA cm −2 by applying a low overpotential of 253 mV for continuous operation of 10 h. Moreover, the CoO x clusters exhibit high intrinsic activity, delivering turnover frequencies of 1.69 O2 s −1 at an overpotential of 300 mV, which are comparable to those of benchmark OER catalysts.